2021
DOI: 10.3390/ani11030800
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Censored or Penalized Data in the Genetic Evaluation of Two Longevity Indicator Traits Using Random Regression Models in North American Angus Cattle

Abstract: This study aimed to evaluate the impact of different proportions (i.e., 20%, 40%, 60% and 80%) of censored (CEN) or penalized (PEN) data in the prediction of breeding values (EBVs), genetic parameters, and computational efficiency for two longevity indicators (i.e., traditional and functional longevity; TL and FL, respectively). In addition, three different criteria were proposed for PEN: (1) assuming that all cows with censored records were culled one year after their last reported calving; (2) assuming that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…e Bayesian framework for analyzing censored survival data [55]; the β-substitution method compared with the Bayesian method [42]; search-and-score-hillclimbing algorithm and constraint-based conditional independence algorithm on censored survival data [43,44]; frequentist and Bayesian approaches to handling censored data and the Markov chain Monte Carlo for imputed data (MCMCid) [46,47]; quantile regression [43,48,49]; random effects hierarchical Cox proportional hazards [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e Bayesian framework for analyzing censored survival data [55]; the β-substitution method compared with the Bayesian method [42]; search-and-score-hillclimbing algorithm and constraint-based conditional independence algorithm on censored survival data [43,44]; frequentist and Bayesian approaches to handling censored data and the Markov chain Monte Carlo for imputed data (MCMCid) [46,47]; quantile regression [43,48,49]; random effects hierarchical Cox proportional hazards [50].…”
Section: Discussionmentioning
confidence: 99%
“…Reference [42] penned down a study aimed at evaluating the impact of different proportions (i.e., 20%, 40%, 60% and 80%) of censored (CEN) or penalized (PEN) data in the prediction of breeding values (EBVs), genetic parameters, and computational efficiency for two longevity indicators (i.e., traditional and functional longevity; TL and FL, respectively). ree different criteria were proposed for PEN: (1) assumed that all cows with censored records were culled one year after their last reported calving; (2) assumed that cows with censored records older than nine years were culled one year after their last reported calving, while censored (missing) records were kept for cows younger than nine years; (3) assumed that cows with censored records older than nine years were culled one year after their last reported calving, while cows younger than nine years were culled two years after their last reported calving.…”
Section: Developments Made To Handle Censored Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Traits that have censored records (e.g., age at first calving and slaughter, longevity) are frequently evaluated in animal breeding programs (Santos et al, 2015;Costa et al, 2019;Oliveira, Miller, Brito, & Schenkel, 2021). In the presence of censoring, the value for a given trait is greater or less than a certain threshold, or belongs to an interval, and it is not possible to observe an exact value for response.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of this database can guide effective management actions for reducing early involuntary culling of dairy cows and perhaps refining current breeding goals. For instance, recent studies in North American Angus cattle reported different variance components and heritabilities estimated for longevity depending on the culling reason ( Oliveira et al, 2020a , 2020b ). Thus, the main objectives of this study were to describe the frequencies of different culling reasons in Canadian Holstein cows and evaluate the impact of systematic factors such as cow age, year, season, province, climate, and ecozone on the frequencies of different culling reasons.…”
Section: Introductionmentioning
confidence: 99%